(untitled) (INNOVATIVE ECONOMY, 2025)
Grynko T.V., Krupskyi O.P., Stasiuk Yu.M. EMOTIONAL DESIGN AS A STRATEGIC MANAGEMENT TOOL IN HOTEL AND RESTAURANT MANAGEMENT Purpose. The aim of this study is to determine the role of emotional design as a strategic management tool in the hotel and restaurant business and to analyse its impact on decision-making efficiency, organizational behaviour adaptability, and cognitive engagement of personnel. Methodology of research. The study applies an interdisciplinary approach combining qualitative content analysis of academic publications, case studies of hotel and restaurant enterprises, cognitive analysis of management patterns, and visual ethnographic research of the spatial-sensory environment. The conceptual foundation is based on the design-based strategic management approach, which enables the assessment of how spatial design solutions influence strategic thinking and behavioural models. Findings. The research revealed that emotional design influences key aspects of management in the hotel and restaurant business: it accelerates decision-making in critical situations, reduces cognitive load on staff, fosters a positive emotional environment for customers, and increases customer loyalty. It was proved that spatial design can act as a latent regulator of team behaviour, supporting self-organization and effective interaction without administrative pressure. Originality. The study proposes an interpretation of emotional design as a framing element of strategic management in service businesses. For the first time, the functional multi-level structure of emotional design (visceral, behavioural, and reflective levels) is generalized and its impact on the cognitive engagement of both staff and clients is defined. Practical value. The recommendations developed for integrating emotional design into hotel and restaurant management strategies can be used to improve service efficiency, enhance internal communication, and establish a sustainable emotional connection with customers. The findings are relevant to both physical and digital service environments. Key words: emotional design, strategic management, hotel and restaurant business, service environment, cognitive engagement, organizational behaviour.